IT Management and Staff Pattern in Special Libraries of Greater Guwahati: A Study - Sarma, Kishor (Indian Journal of Information Sources and Services, 2019)
Information Technology (IT) management ensures better utilization of resources of production i.e. men, machines and materials. Technological change is becoming a driving force in our society. Information technology has a great impact on the functioning of all types of libraries. The services of special libraries also have been drastically changed due to convergence of computing and telecommunication technologies. This paper discusses about the IT management and staff pattern of special libraries of Guwahati.